Environmental fate and aquatic toxicology studies on phthalate esters. - Group, E F (1986)
A comprehensive environmental fate and effects testing program, sponsored by the Chemical Manufacturers Association (CMA) Phthalate Esters Program Panel, has been completed. Based on the results, a preliminary safety assessment has shown that all of the 14 commercially important phthalates tested have sufficiently high safety factors to demonstrate low potential for adverse environmental effects. This program comprised acute toxicity studies on nine representative species of aquatic life, chronic reproduction studies on Daphnia magna, biodegradation (fate) testing, and physicochemical property (mobility) determinations on 14 phthalate esters. The objectives of this program were to determine for each test compound: The concentration at which effects on aquatic life might occur, the potential for bioconcentration in aquatic life, and the relative persistence in the environment. These data would provide the basis for an environmental safety assessment and would identify potential effects that might require further investigation. A total of 195 individual studies were carried out. Tests on a wide variety of aquatic organisms representing different food chain levels in both fresh and salt water environments showed that no single test species was unusually sensitive to the test materials. The higher molecular weight (longer side-chain) phthalates exhibited no toxic effects up to their limits of water solubility in the test systems. Even though the lower molecular weight, more water-soluble phthalates produced toxic effects below their limits of water solubility, no product exhibited unusually severe effects of concern.(ABSTRACT TRUNCATED AT 250 WORDS)